Pallidal and thalamic neurostimulation in severe tardive dystonia. Issue 4 (1st April 2001) - Trottenberg, T; Paul, G; Meissner, W; Maier-Hauff, K; Taschner, C; Kupsch, A
Abstract : A 70 year old woman presented with a 6 year history of medically refractory severe tardive dystonia. After informed consent, a bilateral stereotactic electrode placement targeting the ventral intermediate thalamic nucleus (VIM) and the globus pallidus internus (GPi) was performed. After bilateral stimulation of the GPi, the patient showed a clear and stable improvement of the painful dystonic syndrome within hours. Stimulation of the VIM did not improve the hyperkinetic movements and simultaneous stimulation of both the GPi and the VIM did not result in any additional benefit. The possible pathophysiological mechanisms are discussed.